Celebrity worship and psychological well-being among young adults: Examining the role of self-regulation - Cielo Serquiña; Shania Gwyneth Datu; Pamela Mallari; Ma. Davelyn Barnett (UIN Maulana Malik Ibrahim Malang, 2026)
As young adults become increasingly exposed to digital spaces where celebrities shape trends, identities, and everyday interactions, understanding the psychological implications of celebrity worship has become increasingly important. The study investigates the relationship between celebrity worship and psychological well-being among young adults, examining whether self-regulation moderates this relationship. A total of N=429 Filipino college students, aged 18–25 years were recruited using convenience and snowball sampling. The participants completed an online questionnaire through Google Forms, containing the Celebrity Attitude Scale-7, Ryff's Psychological Well-Being Scale, and the Self-Regulation Scale. Results reveal that celebrity worship negatively predicts psychological well-being (B = -0.4451, p = .027), while self-regulation positively predicts psychological well-being (B = 2.3835, p =